MIGRAÇÃO BOLIVIANA E RELIGIÃO NA CIDADE DE SÃO PAULO: UM ESTUDO SOBRE A PRIMERA IGLESIA BAUTISTA HISPANA DE BRASIL - Paes, André Bezerra (2013)
This research analyzes the impact of religion on a group of Bolivian migrants in the city of São Paulo, who organized a Baptist evangelical community in the region of Pari Primera Iglesia Bautista Hispana de Brasil. In order to accomplish this research, we interviewd some of its church leaders who helped us to understand the organization and we applied 30 questionnaires that enabled us to draw the socioeconomic profile of its members and helped to identify the reasons for their migration and adhesion to this community.